Evaluation of microforming methods for shark skin replication. (May 2014) - Park, Y. W.; Kim, T. W.
<x content-type="archive" xml:space="preserve">Abstract</x> The shark skin has an intriguing three-dimensional rib pattern, which enables the shark to swim fast and efficiently. The alignment of ribs with the water flow direction can maximise drag reduction by decreasing turbulence. In this study, two different replicating forming methods are applied to replicate the shark skin directly: the first is to apply the micromoulding process to obtain both the female replication mould and the shark skin replica; the second method consists of the hot embossing technique for the female replication mould and the micromoulding for the shark skin replica. Then, three- and two-dimensional surface profiles are measured using a stylus profilometer to evaluate the replication precision of the shark skin replicas quantitatively. The results show that the first replication method is more suitable for the production of the shark skin replica.